Effect of Aging on NK Cell Population and Their Proliferation at Ex Vivo Culture Condition - Gounder, Sellamuthu Subbanna; Abdullah, Basri Johan Jeet; Radzuanb, Nur Ezzati Izyan Mohd; Zain, Farah Dalila Mohd; Sait, Nurhidayah Mohamad; Chua, Corine; Subramani, Baskar (Hindawi, 2018)
Age-associated changes in natural killer (NK) cell population, phenotype, and functions are directly attributed to the risk of several diseases and infections. It is predicted to be the major cause of the increase in mortality. Based on the surface density of CD56, NK cells are subdivided into two types, such as CD56 bright and CD56 dim cells, which represent cytokine production and cytotoxicity. In our study, we have examined the age-associated changes in the NK cell population and their subsets at different age groups of males and females (at a range from 41 to 80 years). We found that the total lymphocyte count significantly dropped upon aging in both genders. Although, the level of total immune cells also dropped on aging, and surprisingly the total NK cell population was remarkably increased with the majority of NK cells being CD56 dim . Subsequently, we evaluated the proliferation potential of NK cells and our results showed that the NK cell proliferation ability declines with age. Overall, our findings prove that there is an increase in the circulating NK cell population upon aging. However, the proliferation rate upon aging declines when compared to the young age group (<41 yrs).